Drosophila F-BAR protein Syndapin contributes to coupling the plasma membrane and contractile ring in cytokinesis. Issue 8 (August 2013) - Takeda, Tetsuya; Robinson, Iain M.; Savoian, Matthew M.; Griffiths, John R.; Whetton, Anthony D.; McMahon, Harvey T.; Glover, David M.
Abstract : Cytokinesis is a highly ordered cellular process driven by interactions between central spindle microtubules and the actomyosin contractile ring linked to the dynamic remodelling of the plasma membrane. The mechanisms responsible for reorganizing the plasma membrane at the cell equator and its coupling to the contractile ring in cytokinesis are poorly understood. We report here that Syndapin, a protein containing an F-BAR domain required for membrane curvature, contributes to the remodelling of the plasma membrane around the contractile ring for cytokinesis. Syndapin colocalizes with phosphatidylinositol 4, 5-bisphosphate (PI(4, 5)P2 ) at the cleavage furrow, where it directly interacts with a contractile ring component, Anillin. Accordingly, Anillin is mislocalized during cytokinesis in Syndapin mutants. Elevated or diminished expression of Syndapin leads to cytokinesis defects with abnormal cortical dynamics. The minimal segment of Syndapin, which is able to localize to the cleavage furrow and induce cytokinesis defects, is the F-BAR domain and its immediate C-terminal sequences. Phosphorylation of this region prevents this functional interaction, resulting in reduced ability of Syndapin to bind to and deform membranes. Thus, the dephosphorylated form of Syndapin mediates both remodelling of the plasma membrane and its proper coupling to the cytokinetic machinery.